Aksi Pulau Bersih sebagai Upaya Peningkatan Kesadaran Lingkungan Pesisir di Pulau Samalona Kota Makassar - Nur Islah Sugianto; Nursanti, Nursanti; Wilda Oktaviani; Besse Firma Jamal; Mudasir Zainuddin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Samalona Island is one of the leading marine tourism destinations in Makassar City that faces coastal environmental pollution problems due to the accumulation of waste, particularly plastic debris. Intensive tourism activities, limited waste management facilities, and low environmental awareness among local communities and visitors are the main factors contributing to the decline in coastal environmental quality. This community service program aims to improve the cleanliness of the island’s environment and to enhance the environmental awareness of both the local community and tourists regarding the importance of protecting coastal ecosystems through the Clean Island Action program. The methods employed include beach and shallow-water clean-up activities, environmental education, and evaluation of participant involvement and program outcomes. The activity was conducted on December 6, 2025, on Samalona Island, involving lecturers, students, local residents, and environmental volunteers. The results indicate a reduction in waste volume in coastal and beach areas, as well as increased participation and awareness among participants regarding waste management. This program has generated positive ecological and social impacts and has the potential to serve as a community-based model for sustainable coastal environmental management.